The determinations of household debt in Asia countries [2007-2016] / Nur Syafiqah Shamsudin - Shamsudin, Nur Syafiqah (2019)
Even household debt in several Asia countries might drop from last year but the figure numbers are still high and can increase anytime. This current study employs a Panel Regression Fixed Effect Model in examining the determinants of household debt in Asia countries. This study is using yearly data over the period 2007-2016 for four variables such as Unemployment Rate, Real Interest Rate (RIR), Inflation and Gross Domestic Product (GDP) in modelling the determinants of household debt. The result of this study showed that negative insignificant relationship with household debt. Moreover, a negative significant relationship between inflation and household debt is found. However, there was a positive insignificant relationship of RIR and GDP with household debt.